Tactile stimulation in very preterm infants and their needs of non-invasive respiratory support - Kaufmann, Maxi; Seipolt, Barbara; Rüdiger, Mario; Mense, Lars (Frontiers in Pediatrics, 2022)
Aim: Despite the lack of evidence, current resuscitation guidelines recommend tactile stimulation in apneic infants within the first minutes of life. The aim was to investigate whether timing, duration or intensity of tactile stimulation influences the extent of non-invasive respiratory support in extremely preterm infants during neonatal resuscitation. Methods: In an observational study, we analyzed 47 video recordings and physiological parameters during postnatal transition in preterm infants below 320/7 weeks of gestational age. Infants were divided into three groups according to the intensity of respiratory support. Results: All infants were stimulated at least once during neonatal resuscitation regardless of their respiratory support. Only 51% got stimulated within the first minute. Rubbing the feet was the preferred stimulation method and was followed by rubbing or touching the chest. Almost all very preterm infants were exposed to stimulation and manipulation most of the time within their first 15 minutes of life. Tactile stimulation lasted significantly longer but stimulation at multiple body areas started later in infants receiving prolonged non-invasive respiratory support. Conclusion: This observational study demonstrated that stimulation of very preterm infants is a commonly used and easy applicable method to stimulate spontaneous breathing during neonatal resuscitation. The concomitant physical stimulation of different body parts and therefore larger surface areas might be beneficial.